2019
DOI: 10.1093/neuonc/noz105
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI3K/Akt/mTOR pathway with the pan-Akt inhibitor GDC-0068 in PIK3CA-mutant breast cancer brain metastases

Abstract: Background Activating mutations in the pathway of phosphatidylinositol-3 kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) occur in 43–70% of breast cancer brain metastasis patients. To date, the treatment of these patients presents an ongoing challenge, mainly because of the lack of targeted agents that are able to sufficiently penetrate the blood–brain barrier. GDC-0068 is a pan-Akt inhibitor that has shown to be effective in various preclinical tumor models as well as in clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…Zhao et al 37 found an oncogenic feedforward loop between the p27-Thr198/c-Jun Nterminal kinase2/Signal Transducers and Activators of Transcription3/TWIST axis and AKT, whose activation promoted EMT and cancer metastasis. Franziska et al reported that the pan-AKT inhibitor GDC-0068 inhibited the phosphorylation level of p70S6K-Thr389 and PRAS40-Thr246 residues and reduced the brain metastasis of PIK3CA-mutant breast cancer 38 . These data demonstrated the AKT-mediated pro-cancerous cascades and the potential downstream targets of it in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al 37 found an oncogenic feedforward loop between the p27-Thr198/c-Jun Nterminal kinase2/Signal Transducers and Activators of Transcription3/TWIST axis and AKT, whose activation promoted EMT and cancer metastasis. Franziska et al reported that the pan-AKT inhibitor GDC-0068 inhibited the phosphorylation level of p70S6K-Thr389 and PRAS40-Thr246 residues and reduced the brain metastasis of PIK3CA-mutant breast cancer 38 . These data demonstrated the AKT-mediated pro-cancerous cascades and the potential downstream targets of it in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of PI3K/AKT pathway has been reported to take part in tumor cell proliferation and apoptosis [29][30][31]. Here, we proved that knockdown of miR-489 promoted the activation of PI3K/AKT signaling pathway and miR-489 restoration showed the opposite effect.…”
Section: Discussionmentioning
confidence: 56%
“…PIK3CA encodes p110α, a subunit of phosphoinositide 3-kinase (PI3K), and the proliferation signal from PI3K is transduced to protein kinase B (PKB; AKT) [59,61,62]. In a previous study, the pan-AKT inhibitor GDC-0068 decreased the viability of MDA-MB-453 cells in vitro [63]. Considering that activation of the PI3K/AKT pathway is observed in breast cancer patients with brain metastasis [64,65], this signaling pathway might be a potential target for curing brain metastasis.…”
Section: Discussionmentioning
confidence: 99%